2005
DOI: 10.1159/000088032
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with the Rupture of Tubal Ectopic Pregnancy

Abstract: Objective: To identify risk factors that may lead to the rupture of ectopic pregnancies. Study Design: A retrospective chart review was performed on patients with ectopic pregnancies at the University of Miami/Jackson Memorial Hospital between 1/1/1995 and 3/1/2002. 738 patients were identified with ectopic pregnancies. Women with tubal rupture were compared to those without rupture. Variables analyzed were demographic data, patient-related risk factors (history of pelvic surgery, bilateral tubal ligation, his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 31 publications
3
30
3
2
Order By: Relevance
“…Ruptured ectopic pregnancy was present in 62.3% cases, 24.5% had unruptured ectopic and tubal abortion in 13.9% cases In Latchaw G et al study, tubal rupture was present in 59% cases and 41% had unruptured ectopic pregnancies. They concluded that the patients with a history of a previous ectopic pregnancy are significantly more likely to experience a tubal rupture 24 . Studies have shown that low hemoglobin and hematocrit values, together with higher gravidity at the time of admission, may indicate an increased risk of tubal rupture 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Ruptured ectopic pregnancy was present in 62.3% cases, 24.5% had unruptured ectopic and tubal abortion in 13.9% cases In Latchaw G et al study, tubal rupture was present in 59% cases and 41% had unruptured ectopic pregnancies. They concluded that the patients with a history of a previous ectopic pregnancy are significantly more likely to experience a tubal rupture 24 . Studies have shown that low hemoglobin and hematocrit values, together with higher gravidity at the time of admission, may indicate an increased risk of tubal rupture 25 .…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous studies that reported the number of previous EP as a major risk factor for a new episode of EP. 18,[20][21][22][23][24] Logistic regression showed that seven variables were significantly associated with IUP when compared with EP and SAB combined (age, number of previous EP, parity, a complaint of vaginal bleeding on presentation, number of live births, SAB, and HCG level on presentation). The most significant risk factor found for IUP was parity.…”
Section: Discussionmentioning
confidence: 99%
“…In Latchaw G et al study, the same were 59% and 41% respectively. 20 Laparoscopy and medical therapy have now emerged as the widely used therapeutic modalities with great success in terms of reduced morbidity, shorter hospital stay and conservation of fertility. 21 However choice depends upon early identification of ectopic pregnancy and hemodynamic status of the patients.…”
Section: Discussionmentioning
confidence: 99%